Efficacy of the Stellate Ganglion Block Through the Lateral Approach Using Ultrasonogram and Fluoroscopy - Vinod, Krishnagopal (Turk J Anaesthesiol Reanim, 2018)
OBJECTIVE: Stellate ganglion (SG) block can provide pain relief in sympathetically mediated painful conditions. SG block at the sixth cervical (C6) vertebra level through lateral approach under the ultrasonogram (USG) guidance is very safe but may spare the fibres supplying the upper limb. When the drug is given at the C6 subfascially, it spreads along the cervical sympathetic chain, blocking the head/neck and upper limb. In this study, we assessed the efficacy of the SG block given at the C6 level after confirming the subfascial needle position under USG and downward spread of dye under fluoroscopy. METHODS: Ten patients with sympathetically mediated painful conditions belonging to the American Society of Anesthesiologists (ASA) Class I and II and aged between 18 and 60 years were included in the study. The SG was approached laterally under the USG guidance, and the dye was injected after confirming the subfascial needle position. A downward spread of dye was confirmed on fluoroscope, and 4 mL of 0.25% of bupivacaine with 40 mg of methylprednisolone was injected. Patients were assessed in terms of the pain relief, an increase in axillary temperature and adverse events after 30 minutes. A statistical analysis was done with Student’s t-test and paired samples t-test. RESULTS: There was a statistically significant reduction in the post-block pain scores with the rise in temperature in the ipsilateral arm (p=0.000). The dye spread was observed from the fourth cervical vertebra to the first thoracic vertebra in all patients. Transient hoarseness was seen in 20% of patients, and the sensation of a lump was seen in 10% of patients. CONCLUSION: We conclude that SG can be blocked effectively and safely through the lateral approach at the C6 level under ultrasonogram and fluoroscopic guidance.